Information technology integration in the curriculum of the management course among different universities in Iloilo - Abay, Amy; Arancillo, Lynna; Daulo, Yvonne; Herrera, Elijo Sharon; Pulmones, Rosario; Yu, Michelle Ann
This study aimed to determine the integration of Information Technology in the different universities in Iloilo City, specifically it aimed to find out if there are significant different kinds of information technology programs provided in the management courses ; if there are effects as to application of the IT programs ; and if there competent professors teaching the IT subjects. This study focused only on the effects of the information technology integration in the curriculum of management courses in different universities in Iloilo City.